Odpowiedzi

2010-03-03T16:13:09+01:00
A) 2(a-2b)-7(3a-b)=2a-4b²-21a+7b=-19a-4b²+7b
b) 5(x - y)+ 2(4x+2y)-3(2x+y)=5x-5y+8x+4y-6x-3y=-4y+7x
c) 5(x+2y-3z)- 2(4x-3y+z)=5x+10y-15z-8x+6y-2z=-3x+16y-17z
d) -(k-m-n)+2(k+2m+3n)- kmn=-k+m+n+2k+4m+6n-kmn=-k+5m+7n-kmn
e) 2p(3p-2r)+ 3r(p-2r)=6p²-4pr+3pr-6r²=6p²-pr-6r²
2010-03-03T16:19:08+01:00
A) 2(a-2b)-7(3a-b) = 2a-4b-21a+7b = -19a+3b
b) 5(x - y)+ 2(4x+2y)-3(2x+y)= 5x-5y+8x+4y-6x-3y = 7x-4y
c) 5(x+2y-3z)- 2(4x-3y+z)= 5x+10y-15z-8x+6y-2z = -3x+16y-10z
d) -(k-m-n)+2(k+2m+3n)- kmn= -k+m+n+2k+4m+6n-kmn = k+5m+7n-kmn
e) 2p(3p-2r)+ 3r(p-2r)= 6p²-4pr+3pr-6r² = 6p²-pr-6r²